Growing Up in Hinduism: The Unexpected Transformation of Hinduism in Tolerance and Justice - Putu Satya Narayanti (IAHN-TP Palangka Raya, 2019)
This article is the result of a study of several references that explain the transformation of Hinduism from various perspectives. This paper tries to show the meaning of Hindu tolerance that does not shift as true intrinsic values of the human self. In a pluralistic and heterogeneous society, Hinduism transforms the values of tolerance in a universal perspective of life. Hinduism offers extraordinary diversity through its beliefs, culture, arts, and customs. Claiming more than 1.08 billion adherents or 15% of the world's population. Its diversity offers a freedom that allows individuals to follow many different paths in their quest for God. Hinduism is a religious and cultural phenomenon that breeds tolerance and contains important teachings about values for the modern world. These include beliefs about the sacred earth, belief in the relationship with each other between all life, belief in the law of karma, and other commitments contained in the simplicity of life and spiritual benefits greater than material wealth. Of course, Hinduism still faces many challenges caused by the values of globalism, materialism, consumerism, and individualism. Although much affected by the adverse effects of globalism, Hinduism continues to survive with its theology. The important meaning of Hinduism is basically the most diverse philosophical religion and contains almost every philosophical idea that emphasizes the concepts of self, the world, and God itself. These ideas and ideas form the conceptual background of the uniqueness of Hinduism through the perspective of tolerance.